The role of sulfur and heavier chalcogens in the chemistry of antioxidants. (3rd July 2019) - Amorati, Riccardo; Baschieri, Andrea; Valgimigli, Luca
Abstract: Sulfur chemistry plays a central role in cellular redox homeostasis and cysteine-derived antioxidants like glutathione are the most abundant in biological systems. Inspired by Nature, the insertion of divalent sulfur as a substituent in phenolic antioxidants, e.g in thiatocopherol, seeking for improved antioxidant performance, has been an important strategy for long time. Replacement of sulfur with heavier chalcogens like Selenium and Tellurium has brought to even more performing antioxidants, able to quench peroxyl radical in a catalytic fashion and to express unusually high reactivity. On the other hand, natural bioactive compounds like plant-derived thiosulfinates (R-S(O)S-R) own their exceptional antioxidant properties to the ability of releasing sulfenic acids, whose antioxidant behavior has only recently been clarified. The chemistry and redox properties of unstable sulfenic acids (R-SOH), and analogous selenenic acids (R-SeOH) have also recently been elucidated, to better understand the properties of chalcogen-based natural antioxidants, and to develop novel bio-inspired compounds. This fascinating chemistry will be reviewed and the most significant achievement will be presented. Graphical Abstract: UF0001